DENTAL PRACTICE SAFETY DURING THE COVID-19 PANDEMIC (International journal of artificial intelligence, 2025)
The COVID-19 pandemic has profoundly affected healthcare systems worldwide, including dental practices. Due to the high risk of aerosol transmission in dental procedures, dental professionals are particularly vulnerable to infection. This review aims to assess the safety measures implemented in dental clinics during the pandemic and evaluate their effectiveness in preventing SARS-CoV-2 transmission.Various infection control protocols were adopted, including pre-appointment screening, temperature checks, enhanced personal protective equipment (PPE), high-efficiency particulate air (HEPA) filtration, and strict disinfection procedures. Tele-dentistry also emerged as an important tool, allowing patient consultation and triage without physical contact. Studies report that dental practices that strictly adhered to these protocols successfully minimized transmission risk.Furthermore, modifications in clinical procedures, such as minimizing aerosol-generating treatments and using rubber dams, were widely implemented. Staff training on infection control and proper PPE usage proved crucial for ensuring both patient and healthcare worker safety.Despite these measures, challenges remain. Limited resources, PPE shortages, and patient hesitancy affected the uniform implementation of safety protocols. Psychological stress among dental staff due to infection risk also impacted workflow efficiency.Overall, the pandemic has accelerated the adoption of stringent infection control standards in dentistry. Lessons learned during COVID-19 are likely to influence long-term dental practice safety, emphasizing the importance of preparedness, continuous staff training, and the integration of tele-dentistry. Ensuring a safe environment in dental clinics not only protects healthcare workers but also restores patient confidence in accessing oral healthcare during infectious outbreaks.